The third sector - Hull, Richard, Ph. D. (Emerald, 2011)
The Third Sector is of increasing economic and political interest but has been relatively ignored by Critical Management Studies. The Sector includes charities and a range of organisations such as non-governmental, nonprofit, voluntary and community, but also those trading for a surplus but with prominent social commitments, such as housing associations, credit unions, worker or consumer co-operatives and social enterprises. This book presents cutting-edge international research from a variety of critical perspectives. The chapters include case studies from Japan, South Africa, Canada, Denmark, France, Wales and England, as well as a number of theoretically-based explorations of key issues in the analysis of the Third Sector. The chapters have been developed from presentations and lively discussion at the Critical Management Studies Workshop, Montreal, August 2010. DCMS is an innovative series applying Critical Management Studies to tightly specified topics. Each chapter is followed by a 1,000 word Commentary from a fellow contributor to the volume, and each volume is the product of a collaborative and developmental workshop.
Includes indexes.
Keywords: Nonprofit organizations -- Management.; Nonprofit organizations -- Management -- Case studies.; elektronické knihy; electronic books